Landfill site selection using GIS technology and the analytic hierarchy process - Sekulović, Dragoljub J.; Jakovljević, Gordana L. (Vojnotehnički glasnik / Military Technical Courier, 2015)
Landfills are one of the most common ways of waste disposal. Selecting a landfill site is a complicated and long process that involves a legal framework as well as environmental, economic and social parameters aimed at reducing a negative environmental impact. The landfill site selection in the municipality of Nevesinje (Republic of Srpska), dealt with in this paper, was performed using the analytic hierarchy process (AHP) and GIS technology. Eight criteria were analyzed: geology, distance from settlements, distance from road networks, distance from water bodies, vegetation, slope, elevation and aspect. Relative weighting factors for each criterion were defined by applying the AHP and their linear combinations, with the range of each cell determined by the suitability index. The suitability index has been reclassified in five classes where 67% of the territory belongs to the restricted area, 11% of the territory has low suitability, 6.1% has moderate suitability, 5.9% high suitability, and 10% very high suitability. Two potential landfill sites are proposed, but before a final decision is made, it is necessary to analyze additional parameters.
Keywords: landfill; site selection; AHP; GIS